ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK BERDASARKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, DAN EARNINGS, CAPITAL - Dewi Saptantinah Puji Astuti, Wiwin Sulistyani, Fadjar Harimurti & (Universitas Slamet Riyadi, 2017)
Bank in maintaining customer confidence, the banking institutions need toimprove the health of banks. One bank health maintenance done while maintainingliquidity so that banks can meet its obligations and maintain its performance to thebank always gain the trust of the community. The purpose of this study are: 1) Toanalyze the soundness of PT State Savings Bank Tbk and PT Bank Central Asia Tbkin terms of Risk Profile, Good Corporate Governance, Earnings and Capital. 2) Toanalyze the ratio of bank soundness between PT State Savings Bank Tbk and PTBank Central Asia Tbk in terms of Risk Profile, Earning Good CorporateGovernance and Capital. This research is a case study on PT State Savings Bank Tbkand PT Bank Central Asia, Tbk Period 2013-2015. Sources of data in the study usingsecondary data. Secondary data in this study a financial statement and thepublication of good corporate governance of banking institutions that made theobject of research, obtained through the website of Indonesia Stock Exchange. Dataanalysis techniques used method RGEC. In conclusion that the health of banks interms of Risk Profile, Earning Good Corporate Governance and Capital between PTBank Central Asia Tbk and PT State Savings Bank Tbk years 2013-2015 showed thatPT Bank Central Asia Tbk have better health levels.Keywords: healthy banks, risk profile, good corporate governance, earnings, capital